Assessment of rainfall erosivity with regards to flood occurrence / Janmaizatulriah Jani - Jani, Janmaizatulriah (2003)
In Malaysia, major flood events usually occur during the Northeast and Southeast Monsoon due to continuous heavy rainfall. It is known that the rainfall has a strong correlation with flood occurrences. However, there is no study has been done to correlate the rainfall erosivity and flood occurrences. Therefore in this research the correlation between rainfall erosivity and flood occurrences will be established . Thus, the idea of this research is to get the erosive properties of rainfall; which are the amount , duration, intensity , energy and the erosivity of the rainfall. In this present study , five rivers , which are Klang, Muda, Pahang, Setiu, and Segamat River were selected. Historical rainfall data for three years (1997-1999) were recorded based on the worst cases of historical flood occurrence among the five rivers. The rainfall data during the flood occurrence were obtained from the Department of Irrigation and Drainage. The method adopted in analysing the rainfall erosivity (RE) and rainfall energy is based on the R factor of the Universal Soil Loss Equation. It is expected that the higher rainfall intensity will lead to the higher rainfall erosivity and major flood occurrence. From the results, it has been found that the maximum of 30 minute s rainfall amount affected some result of the rainfall erosivity . A statistical analysis shows that there is a non-linear relationship between rainfall erosivity and rainfall intensity . Transformation of data was employed and positive linear relationship was established between the log erosivity and log intensity and a new equation was obtained linking rainfall erosivity and intensity which is Log RE = 1.172Log RI + 1.118. This equation , within limits can be used as an indicator to predict future flood occurrence with regards to its intensity and erosivity of rainfall for these five rivers .